Modulation of macrophage phenotype and protein secretion via heparin-IL-4 functionalized supramolecular elastomers. (15th April 2018) - Bonito, V.; Smits, A.I.P.M.; Goor, O.J.G.M.; Ippel, B.D.; Driessen-Mol, A.; Münker, T.J.A.G.; Bosman, A.W.; Mes, T.; Dankers, P.Y.W.; Bouten, C.V.C.
Graphical abstract: Abstract: Hallmark of the in situ tissue engineering approach is the use of bioresorbable, synthetic, acellular scaffolds, which are designed to modulate the inflammatory response and actively trigger tissue regeneration by the body itself at the site of implantation. Much research is devoted to the design of synthetic materials modulating the polarization of macrophages, which are essential mediators of the early stages of the inflammatory response. Here, we present a novel method for the functionalization of elastomers based on synthetic peptide chemistry, supramolecular self-assembly, and immobilization of heparin and interleukin 4 (IL-4), which is known to skew the polarization of macrophages into the wound healing "M2" phenotype. Ureido-pyrimidinone (UPy)-modified chain extended polycaprolactone (CE-UPy-PCL) was mixed with a UPy-modified heparin binding peptide (UPy-HBP) to allow for immobilization of heparin, and further functionalization with IL-4 via its heparin binding domain. As a first proof of principle, CE-UPy-PCL and UPy-HBP were premixed in solution, dropcast and exposed to primary human monocyte-derived macrophages, in the presence or absence of IL-4-heparin functionalization. It was demonstrated that the supramolecular IL-4-heparin functionalization effectively promoted macrophage polarization into an anti-inflammatory phenotype, in terms of morphology, immunohistochemistry and cytokine secretion. Moreover, the supramolecular functionalization approach used was successfully translated to 3D electrospun scaffolds for in situ tissue engineering purposes, where UPy-HBP retention, and heparin and IL-4 attachment to the supramolecular scaffolds were proven over 7 days. Lastly, human monocyte-derived macrophages were cultured on 3D scaffolds, which, in case of IL-4-heparin functionalization, were proven to promote of an anti-inflammatory environment on protein level. This study presents a novel method in designing a versatile class of functionalized elastomers that effectively harness the anti-inflammatory behavior of macrophages in vitro, and as such, may be instrumental for the development of a new class of synthetic materials for in situ tissue engineering purposes. Statement of Significance: Macrophages and their phenotypic and functional plasticity play a pivotal role in metabolic homeostasis and tissue repair . Based on this notion, bioactivated materials modulating macrophage polarization were extensively investigated in the past. Here, we designed immunomodulating, synthetic materials based on supramolecular immobilization of a heparin binding peptide, and further bioactivation with heparin and IL-4, an anti-inflammatory cytokine responsible for M2 activation and polarization. Human monocyte-derived macrophages cultured on heparin-IL-4 bioactivated materials displayed an elongated morphology and an anti-inflammatory phenotype, with downregulation of pro-inflammatory cytokines and promotion of anti-inflammatory cytokines over time. This study represents the first step in designing a novel class of synthetic, bioactivated materials that harness the regenerative behavior of host macrophages towards in situ tissue regeneration.